Distribution and clinical significance of anti-carbamylation protein antibodies in rheumatological diseases among the Chinese Han population - Dong, Rongrong; Sun, Yuanyuan; Xu, Wei; Xiang, Weizhen; Li, Meiqi; Yang, Qingrui; Zhu, Ling; Ma, Zhenzhen (Frontiers in Immunology, 2023)
Objective Several studies have demonstrated that anti-carbamylation protein antibodies (Anti-CarPA) are persistent in patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic sclerosis (SSC), primary Sjögren’s syndrome (pSS), and interstitial lung disease associated with RA (RA-ILD). However, the relationship between anti-CarPA and other rheumatic diseases (RDs) and non-RA-ILD is not known till now. This study sought to examine the presence of anti-CarPA in Chinese Han patients with RDs and its clinical significance. Methods The study included 90 healthy controls (HCs) and 300 patients with RDs, including RA, SLE, polymyositis/dermatomyositis (PM/DM), pSS, SSC, spondyloarthritis (SpA), anti-neutrophil cytoplasmic autoantibodies associated with vasculitis (AAV), undifferentiated connective tissue disease (UCTD), and Behcet’s disease (BD). Antibodies against carbamylated human serum albumin were detected using commercial enzyme-linked immunosorbent assay kits. Correlations between clinical and laboratory parameters were analyzed. Result Serum levels of anti-CarPA in RA (34.43 ± 33.34 ng/ml), SLE (21.12 ± 22.23 ng/ml), pSS (16.32 ± 13.54 ng/ml), PM/DM (30.85 ± 17.34 ng/ml), SSC (23.53 ± 10.70 ng/ml), and UCTD (28.35 ± 21.91 ng/ml) were higher than those of anti-CarPA in the HCs (7.30 ± 5.05 ng/ml). The concentration of serum anti-CarPA was higher in patients with rheumatic disease-related interstitial lung disease (RD-ILD), especially RA-ILD, PM/DM-ILD, and pSS-ILD. Patients with RD-ILD who tested positive for anti-CarPA were more likely to have a more severe radiographic classification (grades II, p = 0.045; grades III, p = 0.003). Binary logistic regression analysis suggested that anti-CarPA had an association with ILD in RA (p = 0.033), PM/DM (p = 0.039), and pSS (p = 0.048). Based on receiver operating characteristics (ROC) analysis, anti-CarPA cutoffs best discriminated ILD in RA (>32.59 ng/ml, p = 0.050), PM/DM (>23.46 ng/ml, p = 0.038), and pSS (>37.08 ng/ml, p = 0.040). Moreover, serum levels of anti-CarPA were correlated with antibodies against transcription intermediary factor 1 complex (anti-TIF1) (R = –0.28, p = 0.044), antibodies against glycyl-transfer ribonucleic acid synthetase (anti-EJ) (R = 0.30, p = 0.031), and antibodies against melanoma differentiation-associated gene 5 (anti-MDA5) (R = 0.35, p = 0.011). Conclusion Serum anti-CarPA could be detected in patients with RA, PM/DM, pSS, SSC, and UCTD among the Chinese Han population. And it may also assist in identifying ILD in patients with RA, PM/DM, and pSS, which emphasized attention to the lung involvement in anti-CarPA-positive patients.